The Reality Of Teaching Practices In The Light Of The Theory Of Learning Based On The Brain Teachers And Teachers Of Arabic Language - Mohammed Salman, Huda (Opción, 2019)
The study aims to identify the reality of teaching practices in the light of the the- ory of learning based on the brain for teachers and teachers of Arabic language. The sample of the study consisted of (50) teachers and (40) teachers for prima- ry schools. The results showed no statistically significant differences between the mean responses Sex variable. In light of these results, the researcher recommended focusing on the development of Arabic language teachers on the skill of creating a classroom environment that enhances the characteristics of learning based on the brain and encourages students to achieve learning goals by taking advantage of the characteristics of the hemispheres and employing Arabic teachers for brain dysfunction